Level of Knowledge of Pregnant Women Risk Factors for Occurrence of Low Birth Weight at the Onekore Health Center - Tokan, Pius Kopong (Poltekkes Kemenkes Kupang, 2018)
Background: SDKI 2003, the prevalence of BBLR in Indonesia is about 9%.BBLR generally subjected to the process of life long-term less than good. 2015 BBLR in Ende 169 people (3,73%) of 4.527 live births, with the highest proportion in puskesmas Onekore 35 people (20,71%). Goals and benefits: know the level of knowledge of pregnant women BBLR the risk factors, benefits for public health and the public may minimize BBLR events, to advise on an relevant agencies Method research: the design descriptive quantitative, done at puskesmas Onekore months agustus-september 2017. Sample 79 respondents, simple random sampling system, the instruments the questionnaire, use single variable, namely knowledge pregnant women, univariat analysis. Research result: The average level of knowledge enough 58 respondents (73%), less 21 respondents (27%), awareness levels factors the age of pregnant women and the distance pregnancy against a risk BBLR events good 66 respondents (83%), 23 respondents (29%), factors the condition of pregnant women against a risk BBLR events enough 56 respondents (71%), 23 respondents (29%), factors a problem for pregnant women against a risk BBLR events enough 55 respondents (69%), less 24 respondents (31%), factors on the baby against a risk BBLR events enough by the 53 respondents in (67%), and less 26 respondents (33%). Conclusions: the level of knowledge pregnant women about the incident BBLR risk factors, knowledge enough 58 respondents (73%) and knowledge less 21 respondents (27%).